Effect of corporate governance on institutional investors' preferences: An empirical investigation in Taiwan - Su-Lien Lu; Ying-Hui Li (Journal of Risk and Financial Management, 2019)
This study discusses the institutional investors' shareholding base on corporate governance system in Taiwan. The sample was 4760 Taiwanese companies from 2005 to 2012. Then, this study established six hypotheses to investigate the effects of corporate governance on institutional investors' shareholdings. The panel data regression model and piecewise regression model were adopted to determine whether six hypotheses are supported. For sensitive analysis, additional consideration was given on the basis of industrial category (electronics or nonelectronics), and the 2008-2010 global financial crises. This study discovered that a nonlinear relationship exists between the domestic institutional investors' shareholdings. The managerial ownership ratio and blockholder ownership ratio have positive effects both on domestic and foreign institutional investors. However, domestic and foreign institutional investors have distinct opinions regarding independent director ratios. Finally, the corporate governance did not improve institutional investors' shareholdings during financial crisis periods; instead, they paid more attention to firm profits or other characteristics.
Keywords: 330; institutional investors' shareholdings; panel data model; piecewise regression model; global financial crisis